Murine Rankl−/− Mesenchymal Stromal Cells Display an Osteogenic Differentiation Defect Improved by a RANKL‐Expressing Lentiviral Vector. (1st March 2017) - Schena, Francesca; Menale, Ciro; Caci, Emanuela; Diomede, Lorenzo; Palagano, Eleonora; Recordati, Camilla; Sandri, Monica; Tampieri, Anna; Bortolomai, Ileana; Capo, Valentina; Pastorino, Claudia; Bertoni, Arinna; et al.
Abstract: Autosomal recessive osteopetrosis (ARO) is a severe bone disease characterized by increased bone density due to impairment in osteoclast resorptive function or differentiation. Hematopoietic stem cell transplantation is the only available treatment; however, this therapy is not effective in RANKL‐dependent ARO, since in bone this gene is mainly expressed by cells of mesenchymal origin. Of note, whether lack of RANKL production might cause a defect also in the bone marrow (BM) stromal compartment, possibly contributing to the pathology, is unknown. To verify this possibility, we generated and characterized BM mesenchymal stromal cell (BM‐MSC) lines from wild type and Rankl −/− mice, and found that Rankl −/− BM‐MSCs displayed reduced clonogenicity and osteogenic capacity. The differentiation defect was significantly improved by lentiviral transduction of Rankl −/− BM‐MSCs with a vector stably expressing human soluble RANKL (hsRANKL). Expression of Rankl receptor, Rank, on the cytoplasmic membrane of BM‐MSCs pointed to the existence of an autocrine loop possibly activated by the secreted cytokine. Based on the close resemblance of RANKL‐defective osteopetrosis in humans and mice, we expect that our results are also relevant for RANKL‐dependent ARO patients. Data obtained in vitro after transduction with a lentiviral vector expressing hsRANKL would suggest that restoration of RANKL production might not only rescue the defective osteoclastogenesis of this ARO form, but also improve a less obvious defect in the osteoblast lineage, thus possibly achieving higher benefit for the patients, when the approach is translated to clinics. Stem Cells 2017;35:1365–1377 Abstract : Bone marrow‐derived mesenchymal stromal cells from the Rankl ‐/‐ mouse show an in vitro and in vivo osteogenic differentiation defect as compared to the wild type. Restoration of RANKL production by means of a third generation lentiviral vector expressing human soluble RANKL significantly improves this defect. This finding points to a novel function for RANKL cytokine in the osteogenic process.